2019
DOI: 10.2174/1874836801913010178
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Intelligence Approach for Prediction of Consolidation Coefficient of Soft Soil: A Sensitivity Analysis

Abstract: Background: Consolidation coefficient (Cv) is a key parameter to forecast consolidation settlement of soft soil foundation as well as in treatment design of soft soil foundation, especially when drainage consolidation is used in foundation treatment of soft soil. Objective: In this study, the main objective is to predict accurately the consolidation coefficient (Cv) of soft soil using an artificial intelligence approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The study also suggested to carry out the sensitivity analysis to select the best suitable factors for developing and applying the ML models. The same observation has been pointed out in other studies of Nguyen et al [10] and Pham et al [11]. However, these studies used a trial-manual process for sensitivity analysis, which might not cover all the cases of variation of input parameters.…”
supporting
confidence: 60%
“…The study also suggested to carry out the sensitivity analysis to select the best suitable factors for developing and applying the ML models. The same observation has been pointed out in other studies of Nguyen et al [10] and Pham et al [11]. However, these studies used a trial-manual process for sensitivity analysis, which might not cover all the cases of variation of input parameters.…”
supporting
confidence: 60%
“…ACC is the ratio of the rate number of correct predictions and the total number of predictions [88]. RMSE represents the difference between data observations and data estimates [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Equations for the different measures are given below:…”
Section: Validation Methodsmentioning
confidence: 99%
“…(ii) Data pre-processing: in this step, PCA and the Savitzky-Golay filter were used to reduce the dimensions data and reduce extreme values in the distribution of data. (iii) Data preparation: in this study, the holdout validation method was used for training and validating the models as it is a popular and effective method for generating the datasets for training and testing the models [24,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], and thus the collected data were divided into two parts. The first part included 70% data which was used to train the models, whereas the second part contained 30%, the remaining data and this was used to validate the models as the ratio 70/30 for dividing the training and testing dataset was a common ratio used in applying the ML models [29,[62][63][64][65][66][67][68][69][70][71].…”
Section: Methodology Frameworkmentioning
confidence: 99%